(untitled) (Journal of Event, Tourism and Hospitality Studies, 2022)
Satun is the first geopark in Thailand, recognized by The United Nations Educational, Scientific and Cultural Organization (UNESCO) for having the longest succession of fossils as well as an abundance and diversity of fossil species. It is also renowned for its rich nature, cultural diversity and harmony. Satun geopark has a high potential to be further developed for world tourism. However, the geopark green card is validated only for 4 years. Thailand must ensure a delicate balance between local community development and geopark tourism. The goal of this study is to review existing literature on Satun Geopark’s destination image, visitor expectations, and intended travel dates. It also aims to develop a conceptual framework for evaluating the importance of Satun Geopark’s destination image and visitor expectations. According to the literature, it is clear that tourist expectations and internal motivation have an impact on affective destination image, while external motivation and word of mouth have an impact on cognitive destination image. Cognitive destination image also acts as a mediating factor between external motivation and word of mouth. The results of this study can be used to modify the tourism and information package to maximize tourists’ satisfaction and loyalty. It will also guide the Satun geopark in terms of marketing and providing information to the tourists.